Antispasmodic and vasodilator activities of Morinda citrifolia root extract are mediated through blockade of voltage dependent calcium channels - Aziz Nauman; Yasinzai Masoom; Iqbal Javeid; Mandukhail Saf-; Gilani Anwarul; Khan Aslam; Najeeb- (BMC, 2010)
Abstract Background Morinda citrifolia (Noni) is an edible plant with wide range of medicinal uses. It occurs exclusively in tropical climate zone from India through Southeast Asia and Australia to Eastern Polynesia and Hawaii. The objective of this study was to explore the possible mode(s) of action for its antispasmodic, vasodilator and cardio-suppressant effects to rationalize its medicinal use in gut and cardiovascular disorders. Methods Isolated tissue preparations such as, rabbit jejunum, rat and rabbit aorta and guinea pig atria were used to test the antispasmodic and cardiovascular relaxant effects and the possible mode of action(s) of the 70% aqueous-ethanolic extract of Morinda citrifolia roots (Mc.Cr). Results The Mc.Cr produced a concentration-dependent relaxation of spontaneous and high K+ induced contractions in isolated rabbit jejunum preparations. It also caused right ward shift in the concentration response curves of Ca++, similar to that of verapamil. In guinea-pig right atria, Mc.Cr caused inhibition of both atrial force and rate of spontaneous contractions. In rabbit thoracic aortic preparations, Mc.Cr also suppressed contractions induced by phenylephrine (1.0 μM) in normal- Ca++ and Ca++-free Kerb's solutions and by high K+, similar to that of verapamil. In rat thoracic aortic preparations, Mc.Cr also relaxed the phenylephrine (1.0 μM)-induced contractions. The vasodilatory responses were not altered in the presence of L-NAME (0.1 mM) or atropine (1.0 μM) and removal of endothelium. Conclusions These results suggest that the spasmolytic and vasodilator effects of Mc.Cr root extract are mediated possibly through blockade of voltage-dependent calcium channels and release of intracellular calcium, which may explain the medicinal use of Morinda citrifolia in diarrhea and hypertension. However, more detailed studies are required to assess the safety and efficacy of this plant.